Implications of the pandemic for the construction of nurses' identity based on the journalistic media - Loiza Broering; Maria Itayra Padilha; Roberta da Costa; Maiara Suelen Mazera (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to analyze the work of nurses portrayed in the journalistic media and its impact on the construction of professional nursing identity. Methods: this is qualitative, retrospective, descriptive and documentary research, with 51 reports from Folha de São Paulo. Time frame from March to December 2020. Thematic Content Analysis carried out from Claude Dubar's theoretical perspective. Organization and coding of data performed with the help of ATLAS.ti®. Results: three categories emerged: Working conditions in the pandemic - a problem that worsened; Impacts of the pandemic on daily work; Feelings generated by the pandemic. Conclusions: despite adversities, such as the precariousness of health institutions, inadequate working conditions for nurses, lack of basic items of individual protection, negative feelings and hopelessness, these professionals used their knowledge, skills and innovations in the act of caring, which contributed to reconstructing their professional identity.